Using product platform architecture for identification of part commonality in support of design for modularity - A. B. Abdullah,; A. R. Karnaruddin,; Z. M. Ripin, (2004)
Modular approach is one of the best design techniques as it promotes better and faster designing process. Due to functional independence and physical similarities, it tends to drive platform development. This paper will discuss the application of modularity approach to drive for platform design from a multi-family home appliances product. By utilising the conventional heuristics rules to identify modules, a platform is then developed so that it can be shared among those products. Three consumer products from different family are used as case study. As a result, a new design is proposed with several improvements to the products in terms of part count and part commonality